A Culture of Conspiracy Apocalyptic Visions in Contemporary America. - Barkun, Michael (Berkeley : University of California Press, 2013)
American society has changed dramatically since A Culture of Conspiracy was first published in 2001. In this revised and expanded edition, Michael Barkun delves deeper into America's conspiracy sub-culture, exploring the rise of 9/11 conspiracy theories, the ""birther"" controversy surrounding Barack Obama's American citizenship, and how the conspiracy landscape has changed with the rise of the Internet and other new media.What do UFO believers, Christian millennialists, and right-wing conspiracy theorists have in common? According to Michael Barkun in this fascinating yet d.
10 September II Conspiracies: The First Phase11 September II Conspiracies: The Second Phase; 12 Conspiracy Theories about Barack Obama; 13 Conspiracists and Violence; 14 Apocalyptic Expectations about the Year 2012; 15 Conclusion; Notes; Bibliography; Index
Description based upon print version of record.
Keywords: Millennialism -- United States; Conspiracies -- United States; Human-alien encounters -- United States; Conspiracies -- United States; Human-alien encounters -- United States; Millennialism -- United States; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Electronic books